2018
DOI: 10.1016/j.pacs.2018.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal brain resting-state functional connectivity imaging modalities

Abstract: Infancy is the most critical period in human brain development. Studies demonstrate that subtle brain abnormalities during this state of life may greatly affect the developmental processes of the newborn infants. One of the rapidly developing methods for early characterization of abnormal brain development is functional connectivity of the brain at rest. While the majority of resting-state studies have been conducted using magnetic resonance imaging (MRI), there is clear evidence that resting-state functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 222 publications
(281 reference statements)
0
59
0
Order By: Relevance
“…Photoacoustic Imaging (PAI) is a promising functional and molecular imaging technique for a wide range of biomedical applications [1]. PAI combines the technological advances of both optical and acoustic imaging, i.e., the high intrinsic contrast of optical imaging and the spatial resolution of ultrasound imaging [2,3,49]. Every material, including bodily substances, has a specific optical absorption coefficient unique to endogenous chromospheres in cells [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Photoacoustic Imaging (PAI) is a promising functional and molecular imaging technique for a wide range of biomedical applications [1]. PAI combines the technological advances of both optical and acoustic imaging, i.e., the high intrinsic contrast of optical imaging and the spatial resolution of ultrasound imaging [2,3,49]. Every material, including bodily substances, has a specific optical absorption coefficient unique to endogenous chromospheres in cells [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Photoacoustic imaging (PAI) is a promising imaging technique that combines higher imaging contrast of optical imaging with deeper penetration of ultrasonic imaging [1][2][3]. A nanosecond pulsed laser deposits energy onto a light absorbing sample, causing a local temperature increase and subsequent thermal expansion through the thermoacoustic effect [2,[4][5][6][7][8]. This expansion causes a localized pressure increase, which propagates from the sample to be imaged, by an ultrasound transducer, similar to a traditional ultrasound detection system.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] This in vivo brain functional imaging technique has the following unique advantages: (1) it is an noninvasive imaging mode which is conducted in accordance with ethical principles; (2) animals can maintain normal physiological activity during imaging; (3) it has adequate spatial resolution (up to tens of m), temporary resolution (up to tens of ms) and limited depth of penetration (up to several mm, with intact scalp) in monitoring the brain; (4) it provides high-resolution functional information, such as hemoglobin and blood oxygenation levels relevant to describing physiology and pathology. 6,[8][9][10][11][12][13][14][15][16][17][18][19][20] PAT of small animal brain has successfully been implemented. 3,[8][9][10][11][12][13] In these studies, PAT was used for mapping the microvascular network of a mouse brain with the hemodynamic activities when the scalp and skull were intact.…”
Section: Introductionmentioning
confidence: 99%
“…8,10 Recently, several research demonstrated that the neonatal brain imaging through fontanel using photoacoustic technique is feasible. [14][15][16][17][18][19][20] Even though the skull and scalp of any small animal is thin, the penetration depth is limited. 17,20 In the situation where a limited detection depth is certain, or an endogenous contrast is not available, an exogenous contrast agent can be utilized.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation